Polemik Kritik Wasti terhadap Dominasi Patriakhal dalam Ester 1:9-12 - Yanti, Maria Evvy (STT Iman Jakarta, 2023)
The Book of Esther is one of the books that have a variety of interpretations, especially in interpreting minorities who are faced with genocide amid God's silence. Some interpret the discriminatory treatment received by women as the actions of Queen Vashti, who took the bold step of refusing the king's request in the patriarchal culture. Some interpret that in a patriarchal culture, the ideal wife is obedient and respectful to her husband, but this is not the case with Vashti. Likewise, some interpret Vashti's actions as showing courage, integrity, and self-confidence. The purpose of writing this article is to discover the struggle of Vashti against Xerxes' domination in patriarchal culture. The method used is grammatical analysis from the Chiastic structure. The study results are Help only from God, the integrity of women in patriarchal communities, and women's participation to voice their rights in government life. Abstrak Kitab Ester merupakan salah satu kitab yang memiliki beragam interpretasi, terutama dalam menafsirkan minoritas yang dihadapkan dengan genosida di tengah kebisuan Tuhan. Ada yang menafsirkan perlakuan diskriminatif yang diterima perempuan, ulah Ratu Wasti yang berani mengambil langkah berani menolak permintaan raja dalam budaya patriarki. Ada yang menafsirkan bahwa dalam budaya patriarki, istri yang ideal adalah istri yang patuh dan menghormati suaminya, namun tidak demikian halnya dengan Wasti. Demikian juga, ada yang memaknai tindakan Wasti yang menunjukkan keberanian, integritas, dan kepercayaan diri. Tujuan penulisan artikel ini adalah untuk menemukan perjuangan melawan dominasi Xerxes di tengah budaya patriarki. Metode Metode yang digunakan adalah analisis gramatikal dari struktur kiastis. Hasil penelitian memperlihatkan bahwa pertolongan dari Tuhan, integritas perempuan dalam komunitas patriarki, dan partisipasi perempuan untuk menyuarakan hak-haknya dalam kehidupan pemerintahan.